Level of Uric Acid in Women Suffering from Pre-Eclampsia and its Comparison with Normal Pregnancy - Safia Perveen, Fariha Muzammil, Muhammad Hamza Muzammil, Fizza Mahmood, Muhammad Suleman Azhar, Hina Ilyas, Muhammad Usama Mahmood (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Current study is conducted to explore the variations in uric acid level in pre-eclamptic and normal healthy pregnancy in its third trimester in pregnant females. Methods: This descriptive cross sectional study was conducted to measure the serum uric acid level in mg/dl by kit method. The cutoff value was kept at 5mg/dl. The 10 ml of midstream urine was collected for estimation of urinary protein by dipstick method and graded from +1 to +3. For comparison between two groups in terms of levels of uric acid, independent sample t-test was used. Pearson Chi Square test was used to compare qualitative variables. Results: Raised levels of uric acid were obtained in 81.6% preeclampsia samples, and 13.1% found among normal samples, p<0.01 showed that level of serum uric acid has a significant relationship with preeclampsia. Independent sample t-test showed a significant mean difference for SBP, DBP, and SUA between two groups, (p<0.01) Conclusion: Significant high level of serum uric acid level was found in pre-eclamptic females than normotensive women. The findings suggest that measurement of serum uric acid may be a suitable marker in diagnosis of pre-eclampsia.